Black Protest on the Streets: Visual Activism and the Aesthetic Politics of Black Lives Matter - Nicole Anna Schneider (Current Objectives of Postgraduate American Studies, 2017)
In this article I am reading the visual protest practices of the Black Lives Matter movement as aesthetic and artistic actions which redistribute the sensible, presenting the legacy of slavery and the consciousness of being in the wake. By looking at representations of the movement in press photographs, I am trying to establish the movement’s iconography of protest and the visual strategies employed therein.